Comparative study of analgesic efficacy of levobupivacaine alone and levobupivacaine plus dexmedetomidine in patients undergoing laparoscopic cholecystectomy - Neha Pareek,; Nikita Badmaliya,; Sweta Bharadiya,; Pramila Soni, (Asian Journal of Medical Sciences, 2023)
Background: Instillation of intraperitoneal lignocaine, bupivacaine, levobupivacaine, and ropivacaine has been used, following laparoscopic gynecological and general surgical procedures, to reduce postoperative pain through randomized trials for many years. Aims and Objectives: Intraperitoneal instillation of 0.25% levobupivacaine provides effective analgesia, and we have added dexmedetomidine 1 mcg/kg to compare the analgesic efficacy of levobupivacaine alone and levobupivacaine plus dexmedetomidine in patients undergoing laparoscopic cholecystectomy (LC). Materials and Methods: A total of 120 patients of either sex were included in the study. The age range of the included patients was 25–70 years. All the included patients had the American Society of Anesthesiologists physical status I and II and had to undergo LC surgeries. All patients were randomly divided into two groups of 60 patients each. Results: The mean visual analog scale (VAS) score readings at 4 and 8 h in group A were 21.48±1.80 and 25.41±2.50, respectively, and in group B were 18.14±0.90 and 20.95±1.78, respectively. At 4, 8, and 12 h postoperatively, the mean VAS readings for group B were statistically significantly lower in comparison to the mean VAS readings for group A (P<0.05). Among the A group and B group, the number of patients requiring rescue analgesia was lower in group B in comparison to group A (P<0.05). Conclusion: It was concluded that intraperitoneal instillation of local anesthetic is an easy, cheap, and noninvasive method, which provides good analgesia in the immediate postoperative period after laparoscopic surgery. Adding dexmedetomidine 1 μg/kg to intraperitoneal levobupivacaine 0.25% in LC decreases the postoperative analgesic needs in the postoperative period compared to levobupivacaine 0.25% alone and improves the quality and duration of analgesia.